Collagen Induction Therapy With Dermaroller (Community Based Medical Journal, 2013)
Dermaroller is relatively a new modality for the treatment of acne scars, stretch marks, wrinkles, facial rejuvenation inducing collagen induction by the use of microneedling. Two versions are available: (1) the standard dermaroller version and (2) miniature versions. The principle of using dermaroller modality is to provide collagen induction therapy. Dermaroller is more effective in rolling and boxcar type of scars. It has been shown that rolling with a dermaroller (192 needles, 200 urn length and 70 urn diameter) over an area for 15 times will result in approximately 250 holes/ cm 2 . Microneedling leads to the release of growth factors form new collagen and elastin in the papillary dermis. In addition, new capillaries are formed. The neovascularisation and neocollagenesis lead to reduction of scars. The procedure is aptly called "percutaneous collagen induction therapy" and is also used in the treatment of photoageing. Dermaroller is an extremely effective therapy for post acne scars, even trauma scars. Best results are seen in rolling and box type scars, and even papular scars respond to it. DOI: http://dx.doi.org/10.3329/cbmj.v1i1.13854 Community Based Medical Journal Vol.1(1) 2012 35-37